Soil acidity parameters of laterite soils under rubber - Byju, G.; Varghese, Thomas (Journal of Tropical Agriculture, 2006)
A study was conducted to understand the soil acidity parameters of three selected laterite soils under rubber in Kerala. Pedons were dug to a depth of 2 m at three selected locations viz. Thiruvananthapuram, Angadippuram and Kannur and genetic horizon samples were collected to study various soil acidity parameters. The study showed that all the pedons under investigation have a negative ApH value indicating a net negative surface charge throughout the profiles. Amorphous alumino-silicates could be observed in the surface layers of all three pedons as indicated by high pH (NaF) values. The exchange sites and soil solutions were dominated by exchangeable aluminium and the values were very high in textural-B horizons and hard laterite layers. The base saturation values (sum of cations) for surface horizons were 25.33, 21.90 and 21.57 per cent in pedons at Thiruvananthapuram, Kannur and Angadippuram respectively